The impact of entrepreneurial ecosystems and sustainable digital innovation on business performance: a study of Gilgit-Baltistan Pakistan - Jan, Shahina Qurban; Junfeng, Jiang; Iqbal, Muhammad Babar; Raza, Ali; Naz, Mahek; Bhatt, Tribhuwan Kumar (Frontiers in Sustainability, 2025)
Small and medium-sized enterprises (SMEs) in Gilgit-Baltistan are faced with several critical sustainability-oriented problems within the entrepreneurial ecology. This includes resistance to change, myopic thinking of looking for short-term gains and facing problems accessing advanced technology in a new environment. Thus, this study examines the multifaceted relationships (considering entrepreneurship education, entrepreneurial culture, government support, and social support), sustainable digital innovation, and business sustainability performance, with a particular emphasis on SMEs in rural areas. A total of 13 hypotheses are proposed in this study to examine the above phenomena. Data were collected from 431 participants in Gilgit-Baltistan, Pakistan, through a questionnaire survey, and the data was analyzed using partial least square structured equation modeling (PLS-SEM) to reveal empirical outcomes. The findings acknowledge that the entrepreneurship ecosystem (entrepreneurship education, entrepreneurial culture, government support, and social support) and sustainable digital innovation play a significant role in influencing the performance of sustainable businesses. Furthermore, sustainable digital innovation plays a positive mediating role between the entrepreneurial ecosystem and business sustainability. The research revealed that business sustainability increases with the positive role of different dimensions of the entrepreneurship ecosystem. The findings of this study are discussed within the “ecological modernization theory (EMT)“ and add to the understanding of different sets of relationships that provide a theoretical framework. The study provides ways for different stakeholders in SMEs to handle the entrepreneurship ecosystem, sustainable digital innovation, and sustainable business performance.